Teaching dance studies - Chazin-Bennahum, Judith; Jordan, Melinda (Routledge, 2005)
Teaching Dance Studies is a practical guide, written by college professors and dancers/choreographers active in the field, introducing key issues in dance pedagogy. Many young people graduating from universities with degrees either PhDs or MFAs desire to teach dance, either in college settings or at local dance schools. This collection covers all areas of dance education, including improvisation/choreography; movement analysis; anthropology; theory; music for dance; dance on film; kinesiology/injury prevention; notation; history; archiving; and criticism. Among the contributors included in the volume are: Bill Evans, writing on movement analysis; Susan Foster on dance theory; Ilene Fox on notation; Linda Tomko addresses new approaches to teaching the history of all types of dance; and Elizabeth Aldrich writing on archiving."